Design and implement WSN/IoT smart parking management system using microcontroller - A. E. Hamza; H. H. Qasim; S. A. Alwash; M. M. Fadhel; L. Audah; H. H. Ibrahim; O. S. Hamed; M. I. Hamza; H. A. Saeed (International Journal of Electrical and Computer Engineering (IJECE), 2020)
With the dramatic expansion of new networks such as Wireless Sensor Network (WSN) and Internet-of-Things (IoT), tremendous opportunities have been emerged to incorporate such technologies for valuable tasks. One of these tasks is the smart car parking where there is an imperative demand to manage the parkings in various facilities which may help drivers to save their time. Several research studies have addressed this task using wide range of approaches. However, the energy consumption is still a serious concern. This paper proposes a smart car parking based on cloud-based approach along with variety of sensors. Passive Infrared Sensors (PIRs) have been used to sense the object motion. While Light Dependent Resistor (LDR) sensors have been utilized to sense the light of the parking alarm and display inmformation regarding the occupied and non-occupied parking lots. Finally, multi-micro controller of Arduino have been exploited in order to transmit the information collected to the server. Finally, a prototype Android application has been developed in order to recieve the infromation from the server. Results of simulation showed the efficacy of the proposed method.